Endometriosis-induced alterations in mouse metaphase II oocyte microtubules and chromosomal alignment: a possible cause of infertility - Mansour, Gihan; Sharma, Rakesh K.; Agarwal, Ashok; Falcone, Tommaso (Fertility and sterility, 2010)
To examine the effect of peritoneal fluid (PF) of patients with endometriosis on the cytoskeleton of metaphase II oocytes and correlate the results with the stage of endometriosis and the duration of infertility. Prospective-controlled study. Center for reproductive medicine at a tertiary-care hospital. Women with endometriosis (n=23) and tubal ligation/reversal (n=15). Peritoneal fluid obtained from 38 women (23 with endometriosis and 15 tubal ligation/reversal) after laparoscopy. Four hundred metaphase II oocytes were used: 165 frozen metaphase II oocytes were incubated in the PF of patients with endometriosis, 135 oocytes incubated in the PF of nonendometriosis patients (control subjects) and 100 oocytes incubated in human tubal fluid (HTF) media. Spindle abnormalities (microtubule and chromosomal) were evaluated by confocal imaging. In the endometriosis group, the cytoskeleton had a higher frequency of abnormal meiotic spindle and chromosomal misalignment (score ≥3), indicating severe damage compared with the control groups. The proportions of abnormalities in microtubule and chromosome alterations in endometriosis (67.9% and 63.6%, respectively) were significantly higher than for oocytes incubated with PF of the nonendometriosis group (24.4% and 14.8%) as well as the HTF group (13% and 13%). Oocyte cytoskeleton damage positively correlated with the duration of infertility and the stage of endometriosis. Alteration of oocyte cytoskeleton might be one of the causes of poor oocyte quality in patients with endometriosis.